Effects of flavonoids isolated from Scutellariae radix on cytochrome P-450 activities in human liver microsomes - Kim, JY; Lee, SY; Kim, DH; Kim, BR; Park, RK; Lee, BM (TAYLOR & FRANCIS INC, 2002)
A series of flavonoids isolated from Scutellariae radix were evaluated for their effects on cytochrome P-450 (CYP) activities in human liver microsomes. All flavonoids did not substantially inhibit pentoxyresorufin O-deethylation (CYP2B1), mephenytoin 4-hydroxylation (CYP2C19), dextromethorphan O-demethylation (CYP2D6), and chlorzoxazone 6-hydroxylation (CYP2E1) activities (IC50: >50 muM). Baicalein and 2',5,6',7-tetrahydroxyflavone inhibited hepatic testosterone 6beta-hydroxylation (CYP3A4) activity with a IC50 of 17.4 and 7.8 muM, respectively, Oroxylin A inhibited diclofenac 4-hydroxylation (CYP2C9) activity with a IC50 of 6.1 muM. In contrast, all flavonoids tested inhibited hepatic caffeine N-3-demethylation (CYP1A2) with IC50 values ranging from 0.7 to 51.3 muM. Kinetic analysis revealed that the mechanism of inhibition varied according to the flavonoids, These results suggest that flavonoids tested are inhibitors of hepatic CYP1A2 and that the extracts of Scutellariae radix, widely used as a hepatoprotective agent, may protect the liver through the prevention of CYP1A2-induced metabolic activation of protoxicants.
Keywords: INHIBITION; METABOLISM; ACTIVATION; BENZO(A)PYRENE; MODULATION; BAICALEIN; ENZYMES; WOGONIN; MICE; 1A2